2009
DOI: 10.1038/nphys1197
|View full text |Cite
|
Sign up to set email alerts
|

Imaging nanoscale Fermi-surface variations in an inhomogeneous superconductor

Abstract: Particle-wave duality suggests we think of electrons as waves stretched across a sample, with wavevector k proportional to their momentum. Their arrangement in 'k-space', and in particular the shape of the Fermi surface, where the highest-energy electrons of the system reside, determine many material properties. Here we use a novel extension of Fourier-transform scanning tunnelling microscopy to probe the Fermi surface of the strongly inhomogeneous Bi-based cuprate superconductors. Surprisingly, we find that, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
83
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 28 publications
14
83
1
Order By: Relevance
“…Overall  cross is not dependent on the sample doping/ Fermi surface, but changes throughout each sample in a manner consistent with a continuously changing PAF-zone boundary intersection driven by Fermi surface that varies from patch to patch. This agrees with the measurement of the local variance in q1* measured in Bi-2201 50 . This continuous change suggests that each patch can be modeled as having the equivalent electronic structure as a homogeneous sample consisting of a single  1 value and doping.…”
Section: C Parent Compounds Af-zone Boundarysupporting
confidence: 90%
See 1 more Smart Citation
“…Overall  cross is not dependent on the sample doping/ Fermi surface, but changes throughout each sample in a manner consistent with a continuously changing PAF-zone boundary intersection driven by Fermi surface that varies from patch to patch. This agrees with the measurement of the local variance in q1* measured in Bi-2201 50 . This continuous change suggests that each patch can be modeled as having the equivalent electronic structure as a homogeneous sample consisting of a single  1 value and doping.…”
Section: C Parent Compounds Af-zone Boundarysupporting
confidence: 90%
“…Each patch with the same  1 value will have the same  cross and its value should scale with local effective doping. The 2 nd scenario is supported by previous work that shows the q 1 * modulations wavelength varies locally and that its wavelength depends on the local  1 value of a patch in Bi-2201 50 . Although here we have shown that the q 1 * modulation is confined to a specific energy range.…”
Section: C Parent Compounds Af-zone Boundarysupporting
confidence: 64%
“…2b, but with their components determined in a 'rotating reference frame' set by the local orientation of ϕ. This idea of Fermi surfaces correlated with the local order is supported by the recent STM observations of Wise et al 32 . Focussing only on the electron pocket components, we can write the physical electron operators c α as 7,8 c…”
Section: Introductionsupporting
confidence: 54%
“…1,8,9 STS has revealed that the cuprates have a spatially inhomogeneous electronic structure, including modulations in the LDOS and superconducting gap magnitude. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In the d-wave superconducting phase, the LDOS modulations can arise from quasiparticle interference (QPI), due to the scattering of wave-like quasiparticles off impurities. 12,15,22,[25][26][27] The wavevectors of the modulations can be determined from the Fourier transform of the LDOS.…”
Section: Introductionmentioning
confidence: 99%